PENINGKATAN KEMAMPUAN MENDESKRIPSIKAN PETUNJUK DENAHMELALUI METODE DEMONSTRASI SISWA KELAS IVSDN 006 PAGARAN TAPAH DARUSSALAM - Marsino (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low ability of fourth-grade upper students of SDN 006 Pagaran Tapah Darussalam in describing directive texts. The goal of this study was to improve their ability to describe directive texts through the application of the demonstration method, conducted over a period of one month. The research was carried out at SDN 006 Pagaran Tapah Darussalam, involving 32 fourth-grade students. This classroom action research began in early August 2016. The research instruments consisted of teacher and student activity sheets as well as achievement tests. Based on the data presented in Chapter IV, this study succeeded in improving students’ ability to describe directive texts through the demonstration method. The findings show that the research objectives were achieved. The preliminary data indicated that the average student score before the implementation of the demonstration method was only 65.9. After the demonstration method was applied in the first cycle, the average score increased to 71.6, categorized as “high.” In the second cycle, the average score rose further to 88, also within the “high” category. Moreover, the performance indicators were achieved, with 96.9% of students, or 31 out of 32 students, meeting the completion criteria.